Isotope effect on zonal flow and its configuration dependence in low-density electron-cyclotron-resonance heated plasmas in Heliotron J. (27th August 2021) - Ohshima, S; Okada, H; Zang, L; Kobayashi, S; Minami, T; Kado, S; Adulsiriswad, P; Qiu, D; Matoike, R; Luo, M; Zhang, P; Miyashita, A; et al.
Abstract: The hydrogen/deuterium (H/D) isotope effect on a zonal flow and its configuration dependence are experimentally studied in a helical device, Heliotron J. The isotope dependence of a toroidally symmetric potential fluctuation in the frequency range of <∼4 kHz, a zonal flow, is observed in low-density electron cyclotron resonance heated plasmas in Heliotron J. In the standard configuration, the zonal flow interacting with turbulence is enhanced as the D gas fraction increases. The zonal flow is more dominated against turbulent fluctuation in D plasmas, which should have a favourable impact on turbulence transport. Interestingly, however, the opposite dependence of the zonal flow activity on the isotope ratio is also observed in the different magnetic configurations. The configuration dependence observed in this experiment could be one of the factors to explain the difference in the isotope effect of confinement improvement between tokamaks and helical devices. Impurities and radial electric field, which can also be influenced by isotope mass through the difference in neoclassical transport and plasma-wall interaction, have insignificant influences on the zonal flow behaviour in this experiment.